The Influence of Cultural Practices on Second Language Acquisition: A Mixed-Methods Study - Siti Dila Alfadillah; Alwini; Anis Khoirunisa; Eka Dewi Fithrotunnisa; Eneng Liah Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2025)
This study explores the influence of cultural practices on language learning, focusing on how cultural practices, family structures, and societal values affect the way individuals acquire and use a second language. A mixed-method approach was employed, including both qualitative data from semi-structured interviews and participant observation, as well as quantitative data from language proficiency tests and surveys. The findings reveal significant differences in language acquisition patterns across cultural groups, with collectivist cultures emphasizing formal structures and group-oriented learning, while individualistic cultures highlight self-expression and independent study. Cultural values also influence motivation, peer interaction, and classroom dynamics. The study concludes that cultural practices plays a crucial role in shaping language learning experiences and suggests that educators should tailor their approaches to meet the needs of diverse cultural learners.